Investigation on Diversification, Monitoring Effects, and Banking Mergers - Zhang, Wenjia (Insights into Economics and Management Vol. 7, 2021)
This study investigates the wealth effects of diversification on United States banking mergers and acquisitions announcement. 2,148 domestic US banking M&As announced between 1985 and 2006 are classified based on geographic and activity diversification, and abnormal returns of each group around the merger announcements are examined. The abnormal return equals the daily real return minus the expected return calculated with the market model. I find geographic and activity diversification tends to decrease bidding firms' value, reflected by the bidders' negative abnormal returns around the merger announcement, but increase target firms' value. Target banks are also grouped into private and public companies. In deals consummated with stock, bidders acquiring private targets experience significantly higher cumulative abnormal returns (CARs), measuring the periodic performance and calculated during different event windows encompassed by event days (-n, +n), than bidders acquiring public targets do. It confirms the monitoring hypothesis of private companies, usually with concentrated ownership. The decision-makers should match the business cautiously and time it skillfully to guarantee its stable development and proper positioning. Facing mergers in such a risky industry, regulators should monitor the information disclosure, ensure deal transparency carefully, and provide guidance for both parties, especially in case of diversification.